Application of biostimulants in tomato subjected to water deficit: Physiological, enzymatic and production responses - Mariane Peripolli; Sylvio H. B. Dornelles; Sidinei J. Lopes; Luciane A. Tabaldi; Vinícius S. Trivisiol; Jaíne Rubert (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the effect of the application of the biostimulants Seed+ and Crop+ on physiological and production variables and on the activity of antioxidant enzymes (superoxide dismutase - SOD and guaiacol peroxidase - POD) in tomato plants subjected to two soil water conditions. The experiment was carried out in a greenhouse, in a 2 x 2 x 6 factorial scheme, with two times of application of the biostimulants (flowering and fruiting), two soil water conditions (50 and 100% of soil water holding capacity) and six biostimulants (control treatment; Seed+; Seed+ + Crop+ 1x; Seed+ + Crop+ 2x; Crop+ 1x; + Crop+ 2x). The exprimental design was completely randomized, with four repetitions. The biostimulants Seed+ and Crop+ increased the quantum yield of photosystem II (Fv/Fm), regardless of the time of application and water condition of the soil. The biostimulants Seed+ + Crop+ 2x and Crop+ 2x stood out in the pre-morning period, with an average Fv/Fm of 0.813, under the conditions tested. The highest SOD activity (372.12 U mg-1 of protein) was obtained with Crop+ 2x biostimulant in fruiting and under water deficit. For POD, when under water deficit, the best results were obtained with the biostimulants Seed+ + Crop+ 2x, Crop+ 1x and Crop+ 2x in flowering (810.94; 691.19 and 921.59 U mg-1 protein) and in fruiting (703.60; 800.00 and 972.62 U mg-1 protein). Thus, the use of Seed+ and Crop+ biostimulants can be an alternative to help mitigate the damage caused by water deficit in tomato crop.